2019
DOI: 10.3390/ijerph16193574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orientations, Aspect Ratios, Pavement Materials and Vegetation Elements on Thermal Stress inside Typical Urban Canyons

Abstract: The analysis of local climate conditions to test artificial urban boundaries and related climate hazards through modelling tools should become a common practice to inform public authorities about the benefits of planning alternatives. Different finishing materials and sheltering objects within urban canyons (UCs) can be tested, predicted and compared through quantitative and qualitative understanding of the relationships between the microclimatic environment and subjective thermal assessment. This process can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 94 publications
1
15
0
1
Order By: Relevance
“…For example, Taleghani et al [59] showed that the courtyard provides the most comfortable microclimate in the Netherlands in June compared to other urban forms. Lobaccaro et al [61], through a study in Bilbao, found that the orientation and aspect ratio strongly affected the magnitude and duration of the thermal peaks at pedestrian level, with the vegetation elements improving the thermal comfort. This suggests that there is not a general mitigation strategy using vegetation which could be applied for all scenarios, but ad hoc studies are necessary to optimize the benefits of introducing vegetation for thermal comfort improvement purposes [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Taleghani et al [59] showed that the courtyard provides the most comfortable microclimate in the Netherlands in June compared to other urban forms. Lobaccaro et al [61], through a study in Bilbao, found that the orientation and aspect ratio strongly affected the magnitude and duration of the thermal peaks at pedestrian level, with the vegetation elements improving the thermal comfort. This suggests that there is not a general mitigation strategy using vegetation which could be applied for all scenarios, but ad hoc studies are necessary to optimize the benefits of introducing vegetation for thermal comfort improvement purposes [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…orientation and aspect ratio) significantly affect the intensity and duration of the thermal peaks; green urban infrastructures (i.e. green roofs and green surfaces) strongly improve the thermal comfort conditions and human health [22].…”
Section: Outdoor Thermal Comfort Conditionsmentioning
confidence: 99%
“…A study in Hong Kong to evaluate the cooling performance of various tree species in different urban morphology has suggested that tall trees of low leaf area density (LAD) should be planted in deep canyons and vice-versa for shallow canyons and open-areas [28]. Nevertheless, a few studies have explored the cooling effects of plant combinations on the urban thermal environment [29,30].…”
Section: Accepted Manuscriptmentioning
confidence: 99%